Smart Classrooms as Linguistic Ecosystems: A New Paradigm for Interactive Language Pedagogy - Agung Rinaldy Malik (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study explores the implementation of a smart classroom model conceptualized as a linguistic ecosystem to enhance student engagement in Indonesian language learning within a higher education context. Employing a Design Based Research approach, the study was conducted in three iterative phases involving model design, classroom implementation, and systematic evaluation. A total of 65 undergraduate students aged 18 to 22, along with two Indonesian language lecturers, participated in the study conducted at a major public university in Indonesia. Data collection utilized two validated instruments. The Student Engagement Questionnaire, administered before and after the intervention, measured cognitive, behavioral, emotional, and social engagement through 24 items on a Likert scale. The Interaction Observation Sheet documented observable student behaviors, including the use of multiple modes of communication and collaborative participation, during 14 instructional sessions. Quantitative data were analyzed using paired sample t-tests and Cohen’s d to assess changes in engagement levels, while qualitative data from classroom observations were analyzed thematically to identify patterns of interaction. Findings indicated statistically significant increases across all domains of engagement, with the most notable improvement observed in cognitive engagement. Qualitative analysis revealed a rise in spontaneous language use, peer collaboration, and multimodal communication. These results suggest that a smart classroom designed as a linguistic ecosystem fosters a more interactive and engaging learning environment, supporting deeper student involvement and more dynamic language learning experiences.